Enhancing the antimicrobial efficacy of polyester fabric impregnated with silver nanoparticles using DBD plasma treatment - Ribeiro, Ana Isabel Ferreira (2022)
The functionalization of polyester fabric (PES) with antimicrobial agents presents huge number of potential applications in advanced products. However, the lack of functional groups and the high PES hydrophobicity make the functionalization processes costly, prolonged and requires the use of polluting chemical compounds. In this work, dielectric barrier discharge (DBD) plasma treatment, an affordable and environmental-friendly method, was used to introduce new chemical groups, increase the surface energy and roughness of PES in order to improve the adhesion of silver nanoparticles (AgNPs) in its surface. The PES functionalization was evaluated by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and antimicrobial efficacy against Staphylococcus aureus and Escherichia coli. Despite some additional oxidation, the DBD plasma- treated PES showed superior adhesion of AgNPs and excellent antimicrobial efficacy even after 10 washing cycles (WC).